The Bacterial Spore 2016
DOI: 10.1128/9781555819323.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Chance and Necessity inBacillus subtilisDevelopment

Abstract: Bacillus subtilis is an important model bacterium for the study of developmental adaptations that enhance survival in the face of fluctuating environmental challenges. These adaptations include sporulation, biofilm formation, motility, cannibalism, and competence. Remarkably, not all the cells in a given population exhibit the same response. The choice of fate by individual cells is random but is also governed by complex signal transduction pathways and cross talk mechanisms that reinforce decisions once made.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 111 publications
1
6
0
Order By: Relevance
“…The srfA mutant does not stop only growth but starts to lyse immediately after 12 h. Thereby, in order to survival the cells of srfA would search for a new environment with enough glucose. Indeed, many genes transcription involved in chemotaxis and motility (Mirouze and Dubnau, 2013;van Gestel et al, 2015), were significantly up-regulated in srfA. The result is consistent with the previous report that after nutrients limitation, B. subtilis could synthesize a complex motility and chemotaxis system searching for nutrients in the environment (Hamoen et al, 2003).…”
Section: Mutation Of Srfa Had Obviously An Effect On Ccpa Dependent Ccrsupporting
confidence: 91%
“…The srfA mutant does not stop only growth but starts to lyse immediately after 12 h. Thereby, in order to survival the cells of srfA would search for a new environment with enough glucose. Indeed, many genes transcription involved in chemotaxis and motility (Mirouze and Dubnau, 2013;van Gestel et al, 2015), were significantly up-regulated in srfA. The result is consistent with the previous report that after nutrients limitation, B. subtilis could synthesize a complex motility and chemotaxis system searching for nutrients in the environment (Hamoen et al, 2003).…”
Section: Mutation Of Srfa Had Obviously An Effect On Ccpa Dependent Ccrsupporting
confidence: 91%
“…MAG_08 was classified to the family Bacillaceae (phylum Firmicutes ) with 70.4% of its genes being assigned to the tentative taxon ‘unclassified Bacillaceae ’ at the genus level. Members of the family Bacillaceae are mostly aerobic heterotrophic saprophytes well known for their ecosystem functions in their primary habitat soil [94,95]. These functions include plant–growth–promotion and biocontrol, as well as functions in the carbon and nitrogen cycle.…”
Section: Resultsmentioning
confidence: 99%
“…As endospore-formation is a complex and highly costly procedure (Errington, 2003), it should be favored and prevalent in extreme environments (Abecasis et al, 2013). Indeed, it is a last resort solution, only when other strategies, such as biofilm formation or chemotaxis for example, fail (Mirouze & Dubnau, 2013). It has been shown that only the co-existence of multiple limiting factors increases the relative abundance of EFF in natural springs (Filippidou et al, In preparation).…”
Section: Discussionmentioning
confidence: 99%
“…In order to survive in extreme environments such as volcanic fields, microorganisms have developed diverse survival strategies (Roszak & Colwell, 1987, Mirouze & Dubnau, 2013) such as biofilm formation (Kreft, 2004), morphological plasticity (Justice et al, 2008) or posttranscriptional modifications (Zhao et al, 2002). Another of these strategies that can ensure survival under extreme environmental conditions is endospore formation in Endospore-forming Firmicutes (EFF) (Onyenwoke et al, 2004).…”
Section: Introductionmentioning
confidence: 99%